Preemptive ECMO Cannulation in a Patient with Severe Left Ventricular Systolic Dysfunction Undergoing Cesarean Delivery. (8th April 2019) - Bui, Phuong; Mascaro, P. Gabriel; Henao-Mejia, Juanita; Patel, Selina
Abstract : Obstetric patients with heart failure undergoing cesarean delivery are high risk and the perioperative care of these patients poses significant multidisciplinary challenges. In contrast to the nonobstetric patient population the potential role of mechanical circulatory support in parturients with heart failure is not well established and the use of extracorporeal membrane oxygenation (ECMO) has rarely been reported. We report the case of a super morbidly obese patient with decompensated heart failure, pulmonary hypertension, and superimposed preeclampsia undergoing preemptive ECMO cannulation for urgent cesarean delivery.